Disruptive technologies and curricular flexibility in marketing masters 2019-2020 (Revista de Investigaciones Universidad del Quindío, 2021)
There is a diversity of educational modalities and systems in the study plans and programs in marketing master's degrees in the face of disruptive technologies. In this sense, the general objective is to describe the key characteristics of the study plans in marketing master's degrees 2019-2020 in the face of disruptive technologies, from a descriptive research design based on ten aspects: location, institution, name of the program, profile of admission, graduation profile, curricular structure, field of orientation, didactic orientation, language (in which classes are taught) and duration. The results show that the main characteristics are: curricular structure and didactic orientation. Therefore, it is recommended to consider these aspects to achieve a curricular flexibility that responds to the current context.
Keywords: Disruptive technologies; curricular flexibility; master's degrees in marketing